Polyetheramide Templated Synthesis of Monodisperse Mn3O4 Nanoparticles with Controlled Size and Study of the Electrochemical Properties - He, Lin; Zhang, Geng; Dong, Yuanzhu; Zhang, Zhenwei; Xue, Shihan; Jiang, Xingmao (Nano-Micro Letters, 2014)
Monodisperse Mn3O4 nanoparticles were prepared solvothermally starting from manganese acetate by using polyether amide block copolymers (Pebax2533) as a template in isopropanol. The diameter of the nanoparticles in the range of 8.7 nm∼31.5 nm was decreased with increase of Pebax2533 concentration. The electrochemical properties and application in supercapacitor of Mn3O4 nanoparticles were further studied. The results showed that smaller nanoparticles had a larger capacitance. The higher capacitance of 217.5 F/g at a current density of 0.5 A/g was obtained on 8.7 nm Mn3O4 nanoparticles. The specific capacitance retention of 82% was maintained after 500 times of continuous charge-discharge cycles.